2021
DOI: 10.24095/hpcdp.41.11.03
|View full text |Cite
|
Sign up to set email alerts
|

Applying a gendered lens to understanding self-reported changes in alcohol and cannabis consumption during the second wave of the COVID-19 pandemic in Canada, September to December 2020

Abstract: Introduction Increased alcohol and cannabis consumption and related harms have been reported since the beginning of the COVID-19 pandemic. Existing evidence shows that substance use and related harms differ by gender. Yet, no Canadian study has applied a gendered lens to alcohol and cannabis consumption use during this time. Our objectives were to (1) provide gender-specific prevalence estimates of self-reported increased alcohol and cannabis use; and (2) examine gender-specific associations between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Indeed, younger age, living in an urban area and having co-morbidities of mental health issues were related to an increased likelihood of negative outcomes. [5][6][7] Similarly, Canadian females, especially those who are caregivers of children younger than 18 years, tended to be more seriously affected, a finding that is consistent with international research results. 3 While informative, these findings were restricted by the nature of the data collected, sociodemographic characteristics, a limited set of individual factors (e.g.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, younger age, living in an urban area and having co-morbidities of mental health issues were related to an increased likelihood of negative outcomes. [5][6][7] Similarly, Canadian females, especially those who are caregivers of children younger than 18 years, tended to be more seriously affected, a finding that is consistent with international research results. 3 While informative, these findings were restricted by the nature of the data collected, sociodemographic characteristics, a limited set of individual factors (e.g.…”
Section: Introductionsupporting
confidence: 84%
“…4 This special issue of the journal underscores the negative effects of the first year of the pandemic on Canadians' mental health and well-being. During the first 10 months after the pandemic was officially declared, alcohol and cannabis use 5,6 and depression 7 increased, and selfrated positive mental health, life satisfaction and community belonging 8 declined, with no changes in suicidal ideation noted. 9 However, Canadians were not equally impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Research, policy and practice presents results from the 2020 Survey on COVID-19 and Mental Health (SCMH), 4 a populationbased, cross-sectional survey explicitly designed to address several of the methodological weaknesses of existing evidence. The articles [6][7][8][9][10] in this special issue present urgently needed and reliable populationlevel estimates of mental health during the pandemic as well as comparative analyses quantifying the magnitude and distribution of change in mental health across the population and for select sociodemographic subgroups. Results are extended further by identifying correlates of mental health that are unique to the pandemic, thereby providing greater insights to inform strategies for response, recovery and future preparedness.…”
Section: This Special Issue Of Health Promotion and Chronic Disease Prevention In Canadamentioning
confidence: 99%
“…Second, increases in levels of distress vary across population subgroups and are more pronounced among younger adults, females and immigrant populations. 9,11,[13][14][15] Changes in mental health as a function of socioeconomic circumstances are nuanced: some indicators suggest a positive association between educational attainment and greater increases in levels of distress and alcohol use during the pandemic, relative to before; 9,7,10 while other findings indicate no difference. 8 Third, the prevalence of self-reported suicidal ideation appears not to have increased during the pandemic.…”
mentioning
confidence: 99%
“…In Canada, prior to the pandemic, women were more likely than men to report fair/poor mental health (8.6% vs. 6.7%) [ 56 ], with the pandemic these proportions have increased to 25.5% for women and 21.2% for men [ 56 ]. Additionally, some research suggests that women (compared to men) are more likely to drink alcohol to cope with psychological distress [ 57 , 58 ], while other studies reported significant associations between increased emotional distress and increased alcohol and cannabis use during the pandemic for both men and women [ 59 , 60 ], and only among men [ 61 ]. Thus, it is important to investigate sex-differences in this study.…”
Section: Introductionmentioning
confidence: 99%